The role of antenatal care in predicting health facility delivery among women in Kenya: Further analysis of data from the 2008-09 KDHS - Obago, Irene T. (DHS Working Papers No. 86, 2013)
Improving maternal health remains a priority in Kenya. It is essential in all countries that women have access to high-quality medical care before pregnancy, during pregnancy and childbirth, and afterwards. Timely care could avert many maternal deaths. Despite interventions to promote maternal care, few women use skilled delivery care in Kenya, and maternal mortality rates remain high. While nearly all women have at least one ANC visit, fewer than 50% have the four or more visits recommended by the World Health Organization (WHO). Thus they miss out on key services and tests and do not receive medical advice on possible pregnancy complications. Lack of sufficient antenatal care interrupts the continuum of maternal care. This study examines the role of antenatal care in predicting use of health facilities for delivery among women in Kenya. Data from the 2008-09 Kenya Demographic and Health Survey (KDHS) were analyzed using Stata 11.0 software. Logistic regression was used to run univariable and multivariable analyses. The final multivariable models adjust for maternal age at last birth, education, urban- rural residence, province, level of exposure to mass media, religion, wealth index, and birth order. The study found that both the number of ANC visits and the quality of these visits (based on number of services received) are positive predictors of health facility delivery. Women who received a higher quality of antenatal care (based on an index derived from the number of ANC services received) were from two to four times more likely to deliver in a health facility compared with women who received only one service. Similarly, women with four or more ANC visits were two and a half times more likely than women with no ANC visits to deliver in a health facility. Interventions should target both the supply and demand sides by ensuring that pregnant women know about ANC services to ask for and that health facilities are sufficiently equipped to provide these services.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The DHS Working Papers series is a prepublication series of papers reporting on research in progress that is based on Demographic and Health Surveys (DHS) data. This research is carried out with support provided by the United States Agency for International Development (USAID) through the MEASURE DHS project (#GPO-C-00-08-00008-00). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government. MEASURE DHS assists countries worldwide in the collection and use of data to monitor and evaluate population, health, and nutrition programs. Additional information about the MEASURE DHS project can be obtained by contacting MEASURE DHS, ICF International, 11785 Beltsville Drive, Suite 300 Calverton, MD 20705 (telephone: 301-572-0200; fax: 301- 572-0999; email: reports@measuredhs.com; internet: www.measuredhs.com).